Prevalence of asthma and allergic diseases in adolescents: nine-year follow-up study (2003-2012) - Dirceu Solé; Nelson A. Rosário Filho; Emanuel S. Sarinho; Inês C. Camelo-Nunes; Bruno A. Paes Barreto; Mércia L. Medeiros; Jackeline Motta Franco; Paulo A. Camargos; Javier Mallol; Ricardo Gurgel; Djanira M. de Andrade; Fernanda P. Furlan; et al. (Elsevier, 2015)
OBJECTIVE: To determine the prevalence of symptoms of asthma, rhinitis, and atopic eczema in adolescents (AD; 13-14 years) living in seven Brazilian cities, by applying the standardized written questionnaire (WQ) of the International Study of Asthma and Allergies in Childhood (ISAAC), and to evaluate the time trend nine years after the last assessment of ISAAC phase 3 (ISP3). METHODS: The ISAAC-WQ was answered by 20,099 AD from the Northern, Northeastern, Southeastern, and Southern Brazilian regions. Values obtained were compared to those observed in ISP3 using nonparametric (chi-squared or Fisher) tests, and the ratio of annual increment/decrement was established for each of the centers, according to the symptom assessed. RESULTS: Considering the national data and comparing to values of ISP3, there was a decrease in the mean prevalence of active asthma (18.5% vs. 17.5%) and an increase in the frequency of severe asthma (4.5% vs. 4.7%) and physician-diagnosed asthma (14.3% vs. 17.6%). An increase in prevalence of rhinitis, rhinoconjunctivitis, and atopic eczema was also observed. CONCLUSIONS: The prevalence of asthma, rhinitis, and atopic eczema in Brazil was variable; higher prevalence values, especially of asthma and eczema, were observed in regions located closer to the Equator.